Integrated cell wall and transcriptomic analysis revealed the mechanism underlying zinc-induced alleviation of cadmium toxicity in Cosmos bipinnatus - Yu, Xiao-Fang (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.